Current approach in the prophylaxis and treatment of postoperative thromboembolic events - Arikan, Yuksel; M. Senel, Ferda; Ziyal, Ibrahim; Akman, Yavuz (Annals of Medical Research, 2021)
None
Keywords: s : Thromboembolic events, prophylaxis, heparin